Diastereoselective synthesis of novel 3-aryloxy/alkoxy-4-benzothiazolylpyrazolyl-β-lactams: Potential synthons for novel aminoacids/nanocopolymers. Issue 21 (2nd November 2017) - Bhalla, Jitender; Bari, Shamsher S.; Banik, Bimal K.; Bhalla, Aman
ABSTRACT: A fast, efficient, and diastereoselective synthesis of novel 3-oxo-4-benzothiazolylpyrazolyl-β -lactams is described. The reaction between 2-aryloxy/alkoxyacetic acid and novel benzothiazolylpyrazole-substituted imines afforded exclusive formation of trans -β -lactams. The scope of the reaction was investigated by varying different groups on substrates (R 1, R 2, R 3, Z). All the novel compounds were characterized using various spectroscopic techniques such as FT-IR, 1 H NMR, 13 C NMR, elemental analysis, and mass spectrometry in representative cases. No report has been listed in the literature for the synthesis of these types ofβ -lactam heterocycles so far. GRAPHICAL ABSTRACT: